A City for the Few: A Marxist Criticism Analysis of Class Struggles and Ideology in Zootopia (2016) Movie - Tumiwa, Tessalonika Putri Gracia; Gumanti, Priscilla Aurellia Fensa; Tarihora, Gracia Isabela Sabathini; Syah, Caleb Joshua (Jurnal Pendidikan Makarios, 2026)
Through the lens of Marxist criticism, this study investigates class struggle and ideology as depicted in the 2016 animated feature Zootopia. It aims to reveal how constructed ideologies contribute to shaping class struggles and how false ideologies. The film, which portrays a society divided into predators and prey, was examined to understand how labor exploitation and ideological dominance reflect Karl Marx's and Engel's Marxist theory (1847 & 1867). Qualitative methodology was employed in this study, with data collection focusing on the examination of particular scenes, spoken dialogue, and various cinematic elements: camera positioning, lighting design, and musical accompaniment. As the results: 1) Class Divisions: the film illustrates how societal ideologies, particularly the "predator vs prey" binary, are instilled from a young age, shaping perceptions and forming class divisions. This early indoctrination influences individuals' ideological perspectives and their views of different groups. 2) False Consciousness and Structural Power Abuse: Zootopia demonstrates how false consciousness is formed when individuals accept socially constructed roles as natural, even when these roles are designed to maintain a hierarchy that favors dominant groups. The film shows how structural power and institutions, like the ZPD, are abused to reinforce the "predator vs prey" hierarchy, placing prey in subordinate roles despite their qualifications. 3) Emergence of Class Consciousness and Social Transformation: The study highlights that the exposure of Bellwether's conspiracy results in an "ideological awakening," revealing that the predator-prey conflict is not natural but a constructed political tool. At its core, the paper argues that Zootopia successfully reveals the transformative power of exposing institutional inequalities to awaken collective consciousness and enable societal reform. This study is significant for social awareness of how constructed ideologies in popular media plays a crucial role in shaping how individuals perceive social struggles and inequality.